2019
DOI: 10.3390/app9235245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Toe-Out and Toe-In Gaits on Lower-Extremity Kinematics, Dynamics, and Electromyography

Abstract: Toe-in and toe-out gait modifications have received increasing attention as an effective, conservative treatment for individuals without severe osteoarthritis because of its potential for improving knee adduction moment (KAM) and knee flexion moment (KFM). Although toe-in and toe-out gaits have positive effects on tibiofemoral (TF) joint pain in the short term, negative impacts on other joints of the lower extremity may arise. The main purpose of this study was to quantitatively compare the effects of foot pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Previous research on KAM in TIG has been inconclusive [78,[83][84][85][86]] so these results were not unsurprising. However, a recent study that used musculoskeletal modeling with TIG found no change in JRF even with a decrease in KAM so our results are consistent with their findings [39].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous research on KAM in TIG has been inconclusive [78,[83][84][85][86]] so these results were not unsurprising. However, a recent study that used musculoskeletal modeling with TIG found no change in JRF even with a decrease in KAM so our results are consistent with their findings [39].…”
Section: Discussionsupporting
confidence: 92%
“…A study in healthy controls using TIG without RTB showed a statistically significant reduction in first peak KAM but found no reduction in JRF as estimated by a musculoskeletal model [39]. While some studies have found that KAM may provide a reasonable indicator for the JRF at the first peak of stance, the relationship between KAM and the joint contact force is not as strong for the second peak of stance [20,34].…”
Section: Introductionmentioning
confidence: 99%
“…In our abnormal gait database 2 , 18 healthy volunteers (16 male and 2 female) were recruited and instructed to walk normally and imitate four pathological gait patterns (i.e., toe-in, toe-out, supination, and pronation), following the settings of previous simulation based works [58], [59], [60]. The recruited subjects were with no lower-limb injury history and did not undergo any joint instability during the course of the past six months.…”
Section: A Data Collectionmentioning
confidence: 99%
“…2, the Subjects (6 males, 2 females) were instructed to present different walking styles on a treadmill by supplementary wedged insoles or imitation. It follows the experimental settings similar to existing gait research [2], [36], [37], [38]. In total, five Conditions were considered 1 Experiments were approved by the College Ethics Committee of Imperial College London with the reference No.…”
Section: Multi-view Lower-limb Pose Dataset a Real-world Datasetsmentioning
confidence: 99%